Transportation cost optimization by using linear programming / Nurul Hamizah Pakazi, Nur Syazni Khairul Anuar and Muhammad Ameer Hakim Md Hamidi - Pakazi, Nurul Hamizah; Khairul Anuar, Nur Syazni; Md Hamidi, Muhammad Ameer Hakim (2019)
Transportation cost is very crucial for business that runs transportation services. Proper planning for transporting goods will enhance the outcome of the company. In order to get the optimization for cost of transportation, the company has to consider the cost of transportation occurred. Good planning will result better outcome. In this study, a real-world application of a transportation problem involves transporting goods from warehouse to distributor in Johor, Malaysia has been considered. This study seeks to address the problem to determine the optimal transportation cost for effective planning to guarantee a smooth running of the transporting goods of a business. Therefore, linear programming method is used to ascertain the best route, to maximize the capacity per transportation and to minimize the transportation cost of distributing good from warehouse to distributor. The data that consists of demand and supply requirement are acquired from several branches of one company in Johor. It was interpreted as tableau As the result, the objective to minimize the transportation cost had been achieved by linear programming method compared to the manual calculation It is proven that linear programming is one of the methods that can be used to solve optimization problem by saving the cost about 35%. Nevertheless, demand and supply are not the only constraints for calculating transportation cost, however, other factors need to be considered due to uncertainty.